2017
DOI: 10.1021/acs.cgd.7b00404
|View full text |Cite
|
Sign up to set email alerts
|

Ethyne-Linked Push–Pull Chromophores: Implications of Crystal Structure and Molecular Electronics on the Quadric Nonlinear Activity

Abstract: Three ethyne-linked push–pull materials consisting of a dimethylaniline donor and acceptors of increasing electron-withdrawing strength were prepared as nonlinear optical chromophores. Despite a high similarity of the molecular structures, all three materials featured unrelated non-centrosymmetric crystallization behavior. One of the compounds exhibits a remarkable packing with Z′ = 16 molecules in the asymmetric unit forming two interpenetrating subsystems. Inspection of the nonlinear optical activity of sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The single crystal X-ray structure of 1 is included in the supporting information . The structure of 2 has been published [ 23 , 24 ]. Compound 3 was prepared through Sonogashira coupling of the corresponding iodoarene and terminal alkyne as shown in Figure 3 .…”
Section: Methodsmentioning
confidence: 99%
“…The single crystal X-ray structure of 1 is included in the supporting information . The structure of 2 has been published [ 23 , 24 ]. Compound 3 was prepared through Sonogashira coupling of the corresponding iodoarene and terminal alkyne as shown in Figure 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Neutral pyridine rings are an important structural motif in the construction of molecular crystals and molecular assemblies on surfaces . The ring can serve as 1) CH⋅⋅⋅N hydrogen bond acceptor by using the lone pair of the N atom, 2) CH⋅⋅⋅N bond donor by using the sp 2 ‐CHs of the ring, and 3) π‐system in CH⋅⋅⋅π and π‐π intermolecular interactions by using the ring π‐electrons.…”
Section: Introductionmentioning
confidence: 99%
“…In the crystal structure construction of 4‐ethynylpyridine and its related compounds, CH⋅⋅⋅N bonds involving the strongly acidic sp ‐CHs play an important role . Also, there are many compounds whose structures are stabilized by CH⋅⋅⋅N hydrogen bonds with less acidic sp 2 ‐CH donors . Even very weakly acidic sp 3 ‐CHs can participate in the formation of CH⋅⋅⋅N hydrogen bonds …”
Section: Introductionmentioning
confidence: 99%
“…Recently, we demonstrated that the analysis of the hyperpolarizabilities of individual molecules and their actual orientation in the single crystal is a useful tool to explain macroscopic SHG efficiency of powdered crystals of organic chromophores. 20 Consequently, the static first-order hyperpolarizability tensors β ijk of both molecules were calculated using the Gaussian 09 package. The molecular geometry determined by X-ray diffraction was employed in these calculations ( Fig.…”
mentioning
confidence: 99%